Ekonomi dalam Perspektif Islam - Anwar, Moch. Khoirul (ISLAMICA: Jurnal Studi Keislaman, 2008)
Economic misbehavior would certainly impact on the economic performance of a society. As a religion, Islam realizes this and knows that economic misconduct must be diagnosed. Islam encourages that in order for the economic sustenance to be materialized human and natural resources must be explored to the maximum. Economic sustenance is the goal for any country. And Islam supports a policy toward that sustenance. The fact that Islam loves a strong society means that this religion supports a sound economic policy that would work toward the realization of a well-off society. The QurâÃ¢n states that one must explore the world and seek the providence of God. To âexplore the worldâ is a divine command. The logic behind this command is that, first, one must work to earn fortune so that his worldly needs can be met, and second, he must develop a system so that he may earn the fortune both in legitimate and progressive way. In Islam, working is a form of worship. It is therefore rewarding. But Islam also encourages that we develop a comprehensive, holistic, realistic, just, responsible, and balanced economic system so that our economic sustenance may be realized. Islam believes that the goal of any economic sustenance is the materialization of social and economic welfare. All members of society irrespective of their race, religion and color must benefit from that sustenance.